Diel and seasonal dynamics of Anaulus australis at Muizenberg Beach, South Africa - De Vos, Casha (Department of Biological Sciences, 2025)
This study aimed to expand the geographical range of study the surf zone diatom Anaulus australis in South Africa, focusing on temporal and spatial variations at Muizenberg Beach in False Bay on the south-west coast. The diel cycle of A. australis was studied through hourly samples over 13 hours, by analysing water column and sediment samples at three stations. Phytoplankton cell and chlorophylla concentrations, along with nutrient levels, were assessed. Forecast tidal heights and in-situ wind speed and direction data were incorporated into the analysis. At Muizenberg Beach, the diel cycle persisted even when patches were not visible, with cell concentrations peaking in the morning (mean ± SD: 4.64 ± 6.19x104 cells.mL-1 ) and declining by late afternoon, reaching zero cells.mL-1 by 17:00 at some stations. A large resident benthic population of A. austalis cells was noted (mean ± SD: 160.40 ± 164.51x104 cells.mL-1 of sediment) in comparison to the well-studied Sundays River Beach on the South Coast of South Africa. A. australis concentrations in surface waters decreased further offshore and increased with onshore wind direction and tidal heights, while sediment populations increased towards the station behind the breaker. Wind speed and direction and tidal heights were identified as potential influencers of diatom abundance, but causal links could not be established. In addition to this diel timescale study, a long-term timeseries dataset was collected to establish seasonal patterns in surf zone diatom patches. Photographs of the Muizenberg surf zone at 12-minute intervals were taken for two years (2019-2021) and analysed using machine learning image analysis techniques. Data on the presence of A. australis patch events were generated and a strong seasonal signal was found, with increased prevalence in patch frequency in the winter months (May, June, July), possibly due to increased turbulence. A maximum number of 15 days with patch events were recorded in May 2021. Environmental data were incorporated, and tidal heights were identified as a likely influential factor on patch event frequency. The increased understanding of these diatoms' diel periodicity and seasonal cycles will not only advance our understanding of these organisms but also contribute to broader knowledge of coastal ecosystem dynamics, with potential implications for conservation and management efforts in these critical environments.